'Subjectivity' in newspaper reports on 'controversial' and 'emotional' debates: An appraisal and controversy analysis. Issue 1 (2nd January 2016) - Jakaza, Ernest; Visser, Marianna
ABSTRACT: The notion of 'subjectivity' in news reports has been widely researched, especially from the media perspective. However, 'subjectivity' is realised in various forms and the varied contexts and theoretical approaches offer new understanding of the notion. This article departs from such media-theoretic perspectives to a discourse-linguistic approach and makes an analysis of 'controversial' and 'emotional' reports of debates informed by the Appraisal Theory and Controversy Analysis. The focus of the research is on how the Zimbabwean newspapers represent 'controversial' and 'emotional' debates balancing factuality, impartiality and objectivity. Stories from both independent and state-owned newspapers have been selected on the basis of their 'controversiality' and 'emotionality'. The article concludes that news reporting is directed at aligning and disaligning readers with certain interpersonal meanings. Headlines of newspapers have been argued to be attitudinal or 'emotionally charged'.